2005
DOI: 10.1128/cmr.18.4.757-789.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmas and Ureaplasmas as Neonatal Pathogens

Abstract: SUMMARY The genital mycoplasmas represent a complex and unique group of microorganisms that have been associated with a wide array of infectious diseases in adults and infants. The lack of conclusive knowledge regarding the pathogenic potential of Mycoplasma and Ureaplasma spp. in many conditions is due to a general unfamiliarity of physicians and microbiology laboratories with their fastidious growth requirements, leading to difficulty in their detection; their high prevalence in healthy per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
519
3
25

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(579 citation statements)
references
References 335 publications
14
519
3
25
Order By: Relevance
“…Similar rates of tetracycline resistance were obtained in Germany according to a study involving 469 mycoplasma isolates (179 ureaplasmas and 290 M. hominis) collected over a 20-year period (Krausse & Schubert, 2010), with observed tetracycline resistance rates of 1-3 and 10-13 %, respectively. However, higher tetracycline resistance rates of U. urealyticum isolates (17 %) were reported in China (Zhou et al, 2011), and the 45 % (45/100) prevalence of tet(M) in ureaplasma isolates collected from a broad geographical area of the USA between 2000 and 2004 (Waites et al, 2005) suggests resistance rates even higher than those reported in Tunisia. Taken together, these data indicate a global variation in tetracycline resistance rates, probably due to different practices and policies.…”
Section: Discussionmentioning
confidence: 78%
“…Similar rates of tetracycline resistance were obtained in Germany according to a study involving 469 mycoplasma isolates (179 ureaplasmas and 290 M. hominis) collected over a 20-year period (Krausse & Schubert, 2010), with observed tetracycline resistance rates of 1-3 and 10-13 %, respectively. However, higher tetracycline resistance rates of U. urealyticum isolates (17 %) were reported in China (Zhou et al, 2011), and the 45 % (45/100) prevalence of tet(M) in ureaplasma isolates collected from a broad geographical area of the USA between 2000 and 2004 (Waites et al, 2005) suggests resistance rates even higher than those reported in Tunisia. Taken together, these data indicate a global variation in tetracycline resistance rates, probably due to different practices and policies.…”
Section: Discussionmentioning
confidence: 78%
“…These polymorphic microorganisms that are categorized in the class of mollicutes and order of tenericutes are also characterized by the lack of a cell wall, self multiplication within 1-9 h and genomic size of 600-2,200 kilobases. Of around 200 species available in the class of mollicutes, some are saprophytes with a commensal life in human, animals, insects, plants and some others like Mycoplasma pneumonia, Mycoplasma genitalium, Mycoplasma hominis and Ureaplasma urealyticum are pathogenic species infecting genitourinary and nasopharyngeal tracts (Harasawa et al 2005;Waites et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, urogenital ureaplasma infection is caused by two species, Ureaplasma urealyticum (UU) and Ureaplasma parvum (UP), with a total of 14 serotypes. UU has characteristics of biovar T960T (or biovar 2 or A), and includes 10 large genomic serovars (0.88-1.2 Mbps): 2, 4, 5, 7, 8, 9, 10, 11, 12 and 13, while UP has characteristics of parvo biovar (or biovar 1 or B) and includes four serovars: 1, 3, 6 and 14 [2,3].…”
Section: Introductionmentioning
confidence: 99%